EVALUASI FAKTOR PENYEBAB HUMAN ERROR PADA PERUSAHAAN OTOMOTIF DENGAN PENDEKATAN SHERPA - Silabait, Bergas Maydha; Herwanto, Dene (Universitas Putera Batam, 2025)
PT. XYZ is a company that produces automotive components, especially Bearings. One factor that affects product quality and worker safety during the production process is human error. Addressing this problem requires a systematic approach to identify potential errors and create a corrective plan. The Systematic Human Error Reduction and Prediction Approach (SHERPA), which combines Hierarchical Task Analysis (HTA) and Human Error Identification (HEI), is one approach that can be used. The purpose of this study was to determine the types of human errors that occur during the Bearing production process. Action errors and checking errors were identified as the most frequent types of errors, based on observations and interviews. The analysis resulted in an improvement plan that includes close supervision on the production line, adequate rest periods, not rushing when operating machines, and consistently following regulations and Standard Operating Procedures (SOP). It is hoped that the results of this study will help the company reduce human errors and improve efficiency and safety on the production line.